Pemikiran Fatima Mernisi Tentang Kesetaraan Gender - Anisa Misrida; Sri Suyanta (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to analyze Fatima Mernissi's thoughts on gender equality and their implications for Islamic education. This study is motivated by the persistence of gender inequality in Muslim societies, which are often legitimized through patriarchal-biased religious interpretations. The study uses a qualitative method with a library study approach, with data sources consisting of Fatima Mernissi's works and relevant scientific literature. The data were analyzed using descriptive-analytical analysis techniques with a historical and sociological approach. The results show that Fatima Mernissi affirms Islam as a religion that upholds the principles of justice and gender equality and rejects the subordination of women that stems from social and political constructions. Mernissi uses a critical approach to religious texts, particularly misogynistic hadiths, by placing them in a historical and sociological context. From the perspective of Islamic education, Mernissi's thoughts position education as the primary means of empowering women and establishing just gender relations. The conclusion of the study confirms that gender equality in Islamic education is in line with the basic values ​​of Islamic teachings and needs to be realized through a contextual rereading of religious texts with a justice perspective.